2004
DOI: 10.1074/jbc.m403821200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Transmembrane Segment Zinc Binding in the Structure and Function of Rhodopsin

Abstract: Zinc deficiency and retinitis pigmentosa are both important factors resulting in retinal dysfunction and night blindness. In this study, we address the critical biochemical and structural relevance of zinc ions in rhodopsin and examine whether zinc deficiency can lead to rhodopsin dysfunction. We report the identification of a high-affinity zinc coordination site within the transmembrane domain of rhodopsin, coordinated by the side chains of two highly conserved residues, Glu 122 in transmembrane helix III and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
69
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 46 publications
7
69
0
Order By: Relevance
“…The Leffingwell database contains many odorants that are structurally similar to 11-cis-retinal, such as the strongsmelling irones, ionones and damascones. It is reported that the b-ionone ring of 11-cis-retinal exists 8 Å from a zinc coordination site within the binding site in rhodopsin (Stojanovic et al 2004). With zinc deficiency, the receptor rhodopsin malfunctions; similarly, a lack of zinc causes anosmia.…”
Section: Olfactant Structures: Flexible and Inflexible Moleculesmentioning
confidence: 99%
“…The Leffingwell database contains many odorants that are structurally similar to 11-cis-retinal, such as the strongsmelling irones, ionones and damascones. It is reported that the b-ionone ring of 11-cis-retinal exists 8 Å from a zinc coordination site within the binding site in rhodopsin (Stojanovic et al 2004). With zinc deficiency, the receptor rhodopsin malfunctions; similarly, a lack of zinc causes anosmia.…”
Section: Olfactant Structures: Flexible and Inflexible Moleculesmentioning
confidence: 99%
“…Rhodopsin can directly associate with this bivalent metal ion (5,6), and Zn 2ϩ increases the level of rhodopsin phosphorylation (7). Furthermore, changes are observed in the pattern of thermal bleaching and regeneration of rhodopsin by 11-cis-retinal in the presence and absence of Zn 2ϩ (6,8). Therefore, Zn 2ϩ appears to affect the structure and function of rhodopsin.…”
mentioning
confidence: 98%
“…The role of Zn 2ϩ in vision is likely related, in part, to rhodopsin, the light receptor that initiates phototransduction in the rod outer segments (ROS) 5 of retinal photoreceptor cells (4). Rhodopsin can directly associate with this bivalent metal ion (5,6), and Zn 2ϩ increases the level of rhodopsin phosphorylation (7). Furthermore, changes are observed in the pattern of thermal bleaching and regeneration of rhodopsin by 11-cis-retinal in the presence and absence of Zn 2ϩ (6,8).…”
mentioning
confidence: 99%
“…Zinc levels in the bronchoalveolar lavage fluid and in the isolated alveolar macrophages and epithelial cells were measured using a zincspecific dye FluoZin-3 (Invitrogen, Carlsbad, CA), a recently developed fluorochrome with a high affinity for zinc (K d 15 nM) and little affinity for calcium or magnesium (19,20). This free acid form is not membrane permeable and is mainly used to detect zinc release in extracellular spaces such as lavage fluid.…”
Section: Measurement Of Zinc Levelsmentioning
confidence: 99%